The Study and use of Dynamic Programming (Global Journal of Computer Science and Technology, 2023)
When learning algorithms for the first time dynamic programming is one area that is not well understood but it is also a part that should be studied It has been used effectively in numerous fields such as controlling human movement distributing hydroelectric resources and gene sequencing The dynamic programming principle is explained in detail in this article Comparing it to other algorithms at the same time we are able to comprehend dynamic programming s nature as well as its benefits and drawbacks when compared to alternative techniques for problem-solving On the basis of pertinent application examples it then explores the dynamic programming problem-solving techniques and stages
Keywords: knapsack problem; memory recursion; and dynamic programming